2018
DOI: 10.1097/sih.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Use of Emergency Manuals During Actual Critical Events in China: A Multi-Institutional Study

Abstract: This study demonstrated the nascent success of EM implementation in multiple Chinese institutions. Simulation training enhances the implementation and clinical usage of EM. Simulation training in an operating room was sufficient to learn how to use EM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…One way to increase routine use of EMs is through widespread participation in simulation training events. Studies showed simulations have resulted in successful use of EMs during clinical critical events as reported by anesthesiology residents, with many of them agreeing that EM self-review and immersive simulations positively influenced their subsequent EM use [ 2 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One way to increase routine use of EMs is through widespread participation in simulation training events. Studies showed simulations have resulted in successful use of EMs during clinical critical events as reported by anesthesiology residents, with many of them agreeing that EM self-review and immersive simulations positively influenced their subsequent EM use [ 2 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to facilitate implementation of anesthesia emergency manuals in China, Stanford Operating Room Emergency Manuals, Harvard Ariadne Lab Operating Room Crisis Checklists, and Society of Pediatric and Anesthesia Pedicrisis Critical Events Cards were translated into Chinese [ 8 ]. These manuals were published (December 25, 2015) in the largest anesthesia network in China, namely New Youth Anesthesia Forum, and 125,000 copies were downloaded within the first six months of publication [ 8 ]. Additionally, official Chinese anesthesia organizations endorsed the implementation effort [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One year after multi-institutional implementation a study was performed which shows strong correlation of EM usage to simulation training with roughly 69% of surveyed participant respondents having participated in multidisciplinary simulation training with 70%. These participants reported EM use during at least one critical event in the previous six months with the average number of events being two, proving a largely successful implementation plan and execution as a whole [23]. Additional planning and successful EM implementation through simulation training was completed in 2017 in the form of "Simulation Wars", a competition of sorts including teams, a point system with judges, and awards.…”
Section: Implementation Worldwidementioning
confidence: 98%
“…The implementation of EM was promoted through online forums, conferences, simulation-based training, and competitions. This significantly increased the awareness of Chinese anesthesiologists about crisis in the OR and the willingness to use EM [5,6].…”
Section: Introductionmentioning
confidence: 99%